Clinical outcomes of preoperative chemoradiotherapy in octogenarian with locally advanced rectal cancer - Nishikawa, Takeshi (Mol Clin Oncol, 2019)
The number of elderly patients who receive surgical treatment for rectal cancer has gradually increased with aging of the population. In recent years, preoperative chemoradiotherapy, followed by surgical treatment, has been widely used for treating patients with locally advanced rectal adenocarcinoma. The aim of the present study was to evaluate if preoperative chemoradiotherapy is efficacious and safe for the treatment of rectal cancer in patients older than 80 years. A total of 293 patients with rectal cancer, who received preoperative chemoradiotherapy from 2007 to 2017, were studied. Comorbidities and the short- and long-term outcomes in elderly patients (aged ≥80 years old) were investigated and compared to younger patients. The elderly group comprised of 17 patients (5.8%). Pulmonary disease was the most common comorbidity (23.5%). No significant difference between the two groups regarding the rate of completeness of chemoradiotherapy was detected (P=0.26). Curative resection was performed in 14 patients in the elderly group and 252 patients in the younger group. Among 7 patients from both groups who could not receive curative resection due to their poor general condition, 4 patients had decreased lower respiratory function due to pneumonia (3 patients) or chronic obstructive pulmonary disease (1 patient). Morbidity and mortality rates were similar in elderly and younger groups (35.7% vs. 27.0%, 0% vs. 0%, respectively; P=0.54, P=1.00). No significant difference was found regarding recurrence between the two groups (P=1.00). To conclude, preoperative chemoradiotherapy in elderly patients with rectal cancer is safe and well tolerated.